2010
DOI: 10.1111/j.1865-1682.2010.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

First Reported Incursion of Highly Pathogenic Notifiable Avian Influenza A H5N1 Viruses from Clade 2.3.2 into European Poultry

Abstract: Summary This study reports the first incursion into European poultry of H5N1 highly pathogenic notifiable avian influenza A (HPNAI) viruses from clade 2.3.2 that affected domestic poultry and wild birds in Romania and Bulgaria, respectively. Previous occurrences in Europe of HPNAI H5N1 in these avian populations have involved exclusively viruses from clade 2.2. This represents the most westerly spread of clade 2.3.2 viruses, which have shown an apparently expanding range of geographical dispersal since mid‐200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 8 publications
(7 reference statements)
0
49
0
Order By: Relevance
“…Both sick and asymptomatic infected ducks shed high virus quantities, increasing the risk of transmission. Furthermore, migratory waterfowl have been infected with the Gs/GD lineage of H5N1 HPAI viruses in the field and, based on field epidemiology, such birds have contributed to long-distance virus spread, including intercontinentally, during three distinct time periods: 2005, 2010, and 2014 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Experimental studies in some wild duck species, especially mallards (Anas platyrhynchos), have confirmed their potential to be long-distance vectors of these viruses (17,18).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Both sick and asymptomatic infected ducks shed high virus quantities, increasing the risk of transmission. Furthermore, migratory waterfowl have been infected with the Gs/GD lineage of H5N1 HPAI viruses in the field and, based on field epidemiology, such birds have contributed to long-distance virus spread, including intercontinentally, during three distinct time periods: 2005, 2010, and 2014 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Experimental studies in some wild duck species, especially mallards (Anas platyrhynchos), have confirmed their potential to be long-distance vectors of these viruses (17,18).…”
mentioning
confidence: 96%
“…This lineage of virus has been detected in wild birds through 2012 (26,27). Viruses from this clade 2.3.2.1 probably spread through wild birds to several Asian countries in 2008 and to Europe in 2010 (28). Since 2008, subclade 2.3.4.4 has reassorted with multiple neuraminidase subtypes to form widely circulating H5N2, H5N3, H5N5, H5N6, and H5N8 subtypes of HPAI viruses (22,(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…In addition to the phylogenetic data, presence of wild birds in the proximity of the effected holdings was also reported as further evidence for some of the analysed outbreaks (Bouwstra et al, 2015b;Gall-Recule et al, 2008;Therkildsen et al, 2011). Other sources of evidence presented to support the incrimination of contact with wild birds as the source of introduction were: proximity (epidemiological evidence) (Cecchinato et al, 2010;Cherbonnel et al, 2007;Conraths et al, 2016;Iglesias et al, 2010;Manvell et al, 2008;Marche et al, 2014;Probst et al, 2012;Ward et al, 2008a;Ward et al, 2009b) or phylogenetic inference, where virus was only isolated from the affected poultry holdings and compared with sequences reported in databases such as GenBank (Alexander et al, 2010;Bragstad et al, 2007;Bragstad et al, 2005;Corrand et al, 2012;Handberg et al, 2010;Hanna et al, 2015;Marche et al, 2014;Marinova-Petkova et al, 2016;Parker et al, 2014;Reid et al, 2011;Starick et al, 2008;Szeleczky et al, 2009;Terregino et al, 2007) (Table 5). …”
Section: Risk Of Introduction Associated With Contact With Wild Birdsmentioning
confidence: 99%
“…Most of the reported HPAI H5N1 detections in Eurasian wild birds during the latter half of 2009 were associated with viruses belonging to clade 2.3.2. This represents an evolving and changing epidemiologic dynamic, whereby virus from clade 2.3.2 other than clade 2.2 has apparently spread to wild birds, with potential maintenance and spread through Eurasian wild bird populations (Reid et al, 2010). Therefore, evaluating the sensitivity of Mandarin Ducks to H5N1 clade 2.3.2 virus could provide helpful information to determine the reservoir potential of this species in the current spread of HPAI H5N1.…”
mentioning
confidence: 99%
“…DNA barcoding identified 12 H5N1-positive samples from Mandarin Ducks. The remaining two H5N1-positive samples were from Mallard Ducks or Spotbilled Ducks, which are not distinguishable by DNA barcoding (Lee et al, 2010a (Reid et al, 2010;Sakoda et al, 2010;Kang et al, 2011). Our phylogenetic analysis revealed that the HA genes of the isolates were also classified into clade 2.3.2 and clustered with recent Mongolian isolates (Fig.…”
mentioning
confidence: 99%